Modern facade design for the renovation of Sabilul Muttaqin Mosque, Samarinda City - Hatta Musthafa Adham Putra; Zakiah Hidayati; Raudah Ahmad; Dina Permata Sari; Diky Ramadan (Community Empowerment, 2024)
This community service activity focuses on the planning and design of the renovation of the Sabilul Muttaqin Mosque in Perum Gemilang, Samarinda City. The main objective is to enhance the capacity and aesthetics of the mosque through the expansion of interior spaces, the renewal of a more modern exterior facade, and the replacement of the dome. The method used is a participatory approach, involving the Mosque Committee (DKM) in every stage of planning. The results of field observations and in-depth interviews indicate the need for a flexible multi-functional space and a facade design that combines traditional and contemporary values. The technical drawing documents produced are expected to serve as a reference for the realization of the mosque renovation. The contribution of this activity is expected to provide direct benefits to the congregation and the surrounding community and to serve as a model for mosque renovation planning involving the community.